Disruption of single-copy genes encoding acidic ribosomal proteins in Saccharomyces cerevisiae. - Remacha, M (1990)
Using the cloned genes coding for the ribosomal acidic proteins L44 and L45, constructions were made which deleted part of the coding sequence and inserted a DNA fragment at that site carrying either the URA3 or HIS3 gene. By gene disruption techniques with linearized DNA from these constructions, strains of Saccharomyces cerevisiae were obtained which lacked a functional gene for either protein L44 or protein L45. The disrupted genes in the transformants were characterized by Southern blots. The absence of the proteins was verified by electrofocusing and immunological techniques, but a compensating increase of the other acidic ribosomal proteins was not detected. The mutant lacking L44 grew at a rate identical to the parental strain in complex as well as in minimal medium. The L45-disrupted strain also grew well in both media but at a slower rate than the parental culture. A diploid strain was obtained by crossing both transformants, and by tetrad analysis it was shown that the double transformant lacking both genes is not viable. These results indicated that proteins L44 and L45 are independently dispensable for cell growth and that the ribosome is functional in the absence of either of them.